EKSPERIMENTASI MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING & PEMBELAJARAN LANGSUNG PADA MATERI PELUANG - Reynhart Excel Soentpiet; Vivian E. Regar; Oltje T. Sambuaga (ADIBA : JOURNAL OF EDUCATION, 2022)
This study aims to examine whether the learning outcomes of students who are taught using the Contextual Teaching and Learning model are higher than the learning outcomes of students who are taught using direct learning on opportunity material. This research method is a quasi-experimental design with Posttest only Control Design with a model for context-based learning and instruction and a direct learning model. The results of the Lilliefors test and t-test showed that the data were normally distributed and the final scores of the students of class VIII A as the experimental class and VIII B as the control class had substantial variations in the average score. The results were analyzed using t-test with a significance level of = 0.05 is Tcount = 2.06336 > Ttable = 2.01063 so that H_0 is rejected and H_1 is accepted. Thus the application of the Contextual Teaching and Learning learning model has an effect on students' ability to solve Opportunity questions at St. Catholic Junior High School. Johanis Laikit.